An investigation into the pathogenesis of blue catfish alloherpesvirus in ictalurid catfish. Issue 2 (18th September 2021) - Dharan, Vandana; Khoo, Lester; Phelps, Nicholas B. D.; Kumar, Ganesh; Steadman, James; Bosworth, Brian; Aarattuthodi, Suja
Abstract: Intensive aquaculture production systems often encounter infectious viral disease outbreaks causing substantial fish mortalities and associated economic losses. Blue catfish alloherpesvirus (BCAHV) is an Ictalurid herpesvirus with limited information on pathogenesis. To determine the host‐specificity and potential host range of BCAHV, the virus was inoculated onto various fish cell lines belonging to families Ictaluridae, Cyprinidae, Centrarchidae, and Clariidae. Viral replication and exhibition of cytopathic effects (CPEs) were restricted to cell lines from the family Ictaluridae indicating the host preference of BCAHV. Subsequently, fish challenges were conducted to evaluate intrinsic and extrinsic factors influencing BCAHV infection. Mortality because of BCAHV infection was significantly higher in blue catfish and least in channel catfish further specifying the host preference of the virus. Histopathological assessment of the BCAHV infected fish revealed splenitis with severe erythrophagia. Host susceptibility to BCAHV differed with age with fish at 60 days post hatch being more susceptible. Temperature had a significant role in the activation and pathogenesis of BCAHV. Fish exposed to BCAHV at a sustained high temperature had significantly low mortality suggesting the likelihood of virus inactivation. Virus exposure in tanks with high stocking density resulted in significantly high fish mortalities indicating horizontal transmission is a key element in BCAHV pathogenesis. The heightened pathogenicity of BCAHV in blue and hybrid catfish as observed in this study validates its potential to be a significant pathogen in catfish production.